Design of portable recyclable drainboard set-up. Issue 1 (July 2021) - Sun, Zhuoqi; Wang, Mingyuan; Wang, Kuanjun; Xi, Zunbang; Li, Guo; Fu, Yuchen; Wang, Yajun
Abstract: For the traditional drainboard set-up device obvious disadvantages: the structure is bulky, loading complex, often need drainage plate body, affecting the drainage effect, almost impossible to recycle, poor environmental protection performance, due to the effect of deformation, late work and other devices have interference, the drainage itself difficult to regulate in the process of setting up. In order to achieve the light, automatic, non-destructive and recyclable of drainage plate, improve the obvious shortcomings mentioned above, a series of improvements are made to the drainage plate set-up device. Through the verification of laboratory experiments, the problems such as large, bulky, high vulnerability and low recovery rate are solved, and the laboratory simulation has no suitable equipment, which reduces the space occupancy rate, saves resources and so on, and greatly reduces the cost of experiments. In water engineering applications, this new type of drainboard discount ingress than the existing drainboard plug-in machine, can be a good substitute for improving the status quo of the project.